DAYA HAMBAT INFUSA BIJI PINANG (Areca catechu L.) TERHADAP BAKTERI Staphylococcus aureus - Maryam Ulfah Wael; Sri Sinto Dewi; Endang Tri Wahyuni Maharani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The objective of this research is to measure and analyze the difference of inhibition concentration of areca nuts concentration 2%b/v, 3%b/v, 4%b/v,5%b/v and 6%b/v on the growth of S.aureus. The sample used in this research isareca nuts (Areca catechu L.) with the object of research S.aureus that hasequalized turbidity with Mc Farland standard 0.5. Antibacterial testing is doneby diffusion method (wells). The results showed that areca nuts can inhibitS.aureus bacteria with area of inhibit zone for concentration 2% b/v, 3% b/v,4% b/v, 5% b/v and 6% b/v is 14,5 mm, 14,6 mm, 16 mm, 18 mm and 18 mm.Result of normality test Kolmogorov-Smirnov S.aureus (p=0,691) the valuesobtained are normally distributed. The homogenity test of S.aureus is nothomogeneous, Then proceed with non parametric test that is Kruskal Wallis(p=1,000) the values obtained showed no significant difference to meaninhibition zone diameter between concentrations 2%b/v, 3%b/v, 4%b/v, 5%b/vand 6%b/v areca nuts infusion against S. aureus bacteria. Keywords: Areca nuts infusion, Staphylococcus aureus, Inhibition